ISOLATION OF NEW 1DS/1RS WHEAT_RYE RECOMBINANTS (ISOLASI REKOMBINAN BARU GANDUM-RYE 1DS/1RS) - Dwi Ratna Anugrahwati1 (CROP AGRO, Scientific Journal of Agronomy, 2009)
ABSTRACT The wheat-rye translocation 1DL.1RS has been used to introduce stem rust disease resistance associated with the 1RS chromosome, however, cultivars carrying this translocation exhibit deleterious end-use quality. The aim of the experiment was to screen and isolate additional wheat-rye recombinants, in order to eliminate or reduce these deleterious effects of the rye chromosome 1RS when transferred to wheat. Besides their potential use in wheat improvement, a series of new wheat-rye recombinants could find application in mapping activities with other genes. Using the presence of the SEC‑1 marker as an indication of the 1RS chromosome segment, several suspected recombinants were isolated. The frequency of recovery of suspected recombinants of phenotypes “TRI‑D1+GLI‑D1-SEC‑1+” and “TRI‑D1-GLI‑D1+SEC‑1+” ranged from 0.6 to 6 % in families 1 to 3. However, family 4 showed a much higher than expected frequency of these suspected recombinant chromosomes (24.4%). A model was proposed to explain the nature of Family 4 based on homozygosity for the 1DL.1RS translocation and the presence of two recombinants chromosomes involving the short arm of group 1 chromosomes. ABSTRAK Translokasi gandum-rye 1DL.1RS digunakan untuk mengintroduksi ketahanan terhadap penyakit karat batang yang terletak pada kromosom 1RS, tetapi kultivar pembawa tranlokasi ini menunjukkan kualitas produk akhir yang jelek. Penelitian ini bertujuan untuk mengidentifikasi dan mengisolasi rekombinan gandum-rye baru, untuk mengurangi efek kurang menguntungkan dari kromosom 1RS ini jika ditransfer ke tanaman gandum. Disamping pentingnya dalam perbaikan kualitas gandum, serangkaian rekombinan akan bermanfaat bagi kegiatan pemetaan gen-gen lain. Dengan menggunakan marker protein SEC-1 sebagai indikator keberadaan segmen kromosom 1RS, beberapa rekombinan telah diisolasi. Frekuensi rekombinan “TRI‑D1+GLI‑D1-SEC‑1+” dan “TRI‑D1-GLI‑D1+SEC‑1+” berkisar 0.6 – 6% pada famili 1-3, tetapi famili 4 menunjukkan frekuensi jauh lebih tinggi (24.4%). Suatu model dirancang untuk menjelaskan keadaan ini berdasarkan homosigositas translokasi 1DL.1RS dan keberadaan 2 rekombinan kromosom yang melibatkan lengan pendek kromosom grup 1 pada gandum.